Does distress predict central sensitisation in people living with HIV? - Mqadi, Luyanduthando (Department of Psychiatry and Mental Health, 2024)
Background Persistent pain is a frequent complaint associated with compromised mental health in many people with HIV (PWH). Central sensitisation (CS) is a hallmark of most persistent pain conditions. Pain and psychosocial distress (PSD) appear to have a bidirectional relationship. Therefore, it is plausible that PSD contributes to pain by increasing central sensitisation (CS), thus maintaining pain in PWH; however, this hypothesis has not been tested. Experimentally induced secondary hyperalgesia (SH) has been used in the laboratory study of other pain conditions (e.g., neuropathic pain) to increase understanding of CS mechanisms. Therefore, the model of SH is useful for investigating pain related to CS, such as pain associated with HIV. NMDA antagonists are often used to prevent and treat pain associated with CS based on the evidence from animal and human pain studies. Evidence suggests that NMDA antagonists likely target mechanisms underlying clinical pain, specifically wind-up, allodynia and hyperalgesia. However, the effect of NMDA antagonists on SH is under-recognised and poorly understood. Understanding the effect of NMDA antagonists on SH would help to inform the appropriate matching of treatment to individuals. We conducted two studies. First, a systematic review according to PRISMA guidelines on the existing evidence that targeting the NMDA system alters experimentally induced SH, in healthy human participants. Second, we conducted an experimental study to investigate whether distress predicted central sensitisation in people living with HIV (PWH). Methods Systematic review: The influence of NMDA targeting pharmacological manipulations on experimentally induced SH in healthy human adults without clinical pain We identified studies that recruited healthy, pain-free human participants and experimentally induced SH (magnitude of SH, surface area of SH) and used a pharmacological method known to target the NMDA system to manipulate SH. Studies were identified by searching various electronic databases (conducted on the 24th of June 2019, updated on the 29th of September 2022). We also checked reference lists and contacted experts in the field, including authors who have recently published narrative reviews on experimental induction and manipulation of SH, to identify studies missed through electronic searching. We included studies that were published and in-press or accepted records with titles, abstracts, and full-text versions available in English. Authors were asked to provide missing data where necessary. Two or more reviewers assessed the risk of bias, extracted data, and judged the quality of evidence (GRADE) of the included studies. Data analysis was performed by narrative summary, and if more than two studies were available for a given manipulation, data were included in the meta-analysis. Data were pooled in subgroups by study design and the type of manipulation (e.g., ketamine) for each outcome (magnitude of secondary hyperalgesia, area of secondary hyperalgesia, or both). We generated funnel plots to examine publication bias. Experimental study: Does distress predict central sensitisation in PWH? We aimed to investigate the relationships between PSD, SH (a known human surrogate model of CS), and persistent pain in PWH. We recruited consenting adults with well controlled HIV, reporting either persistent pain or no pain (assessed using a modified Brief Pain Inventory). Participants provided self-reports of PSD severity (on the Hopkins 25-item scale). We used high-frequency electrical stimulation to induce SH on one pain-free forearm and assessed the surface area (primary outcome) and magnitude (secondary outcome) of SH using a von Frey filament and ‘pinprick' rods, respectively. It was hypothesised that the surface area and magnitude of experimentally induced SH would be positively associated with PSD severity (hypothesis 1) and that the persistent pain group would have a greater surface area and magnitude of experimentally induced SH than the group without pain (hypothesis 2). Results Systematic review: The influence of NMDA targeting pharmacological manipulations on experimentally induced SH in healthy human adults without clinical pain Twenty-nine records were included in this review. Some records reported multiple manipulation methods, so each yielded multiple datasets. Therefore, the 29 records yielded 52 datasets. The effect of NMDA antagonists on experimentally induced SH was assessed by change in magnitude of SH in three records (4 of 52 studies) and assessed by surface area of SH in 20 records (37 of 52 studies). Six records (11 of 52 studies) assessed by change in surface area of SH. Six records (11 of 52 studies) assessed both the change in magnitude and surface area of SH in response to NMDA antagonist administration. Narrative summary Twelve studies manipulated the magnitude of SH using ketamine alone (n = 10) or combined with alfentanil (n = 2). Seven reported no effect, and three found a decrease in the magnitude of SH. Combining ketamine and alfentanil had no effect on the magnitude of SH. Thirty-five studies manipulated the surface area of SH using ketamine alone (n = 31) or combined with alfentanil (n =2), morphine (n = 1) or remifentanil (n = 1). Of those using ketamine alone, fifteen reported no effect, and sixteen found a decrease in the surface area of SH. Combining ketamine with alfentanil or morphine had no effect on the surface area of SH; however, the combination of ketamine and remifentanil decreased the surface area of SH. Ten studies manipulated the surface area of SH using dextromethorphan alone (n = 8) or combined with morphine (n = 2). Four of those using dextromethorphan alone reported no effect, and the rest reported a decrease in the surface area of SH. Those who combined dextromethorphan with morphine reported no effect (n=1) or a decrease (n=1) in the surface area of SH. Studies that used CH3381 (n = 1) or neramexane (n = 1) reported a decrease in the surface area of SH. One study that used magnesium sulphate found no effect of magnesium on the surface area of SH. Meta-analysis Forty studies (seven assessing the magnitude of SH) were included in the meta-analysis. Ketamine had no effect on the magnitude of SH. Similarly, ketamine, CHF3381, and dextromethorphan had no effect on the surface area of SH. Experimental study: Does distress predict central sensitisation in PWH? There was a positive relationship between PSD severity and the surface area of SH; however, the surface area was not predicted by pain status. There was no relationship between PSD severity and the magnitude of SH. Our plots suggested that the ‘pain' group had a stronger positive relationship between PSD and the magnitude of SH than the ‘no pain' group. However, we couldn't confirm this because we couldn't find a suitable statistical model. The proportion of participants reporting pain developed a greater magnitude of SH than those without pain. In contrast, the proportion of participants without pain developed a greater surface area of SH than those with pain. Conclusion Systematic review: The influence of NMDA targeting pharmacological manipulations on experimentally induced SH in healthy human adults without clinical pain The results of this study indicate that NMDA antagonists have no effect on the surface area or magnitude of experimentally induced SH. These findings carry important implications for clinical practice, highlighting the limited efficacy of NMDA antagonists in modulating SH. Future studies should explore alternative pharmacological and non-pharmacological interventions to assess their potential in modulating SH and optimising patient outcomes. Experimental study: Does distress predict central sensitisation in PWH? Psychosocial distress predicted the surface area but not the magnitude of SH in individuals living with HIV, independent of pain status. The positive relationship between the surface area of SH and PSD may support targeting of PSD to reduce pain. Specifically, interventions aimed at reducing PSD may hold therapeutic potential in addressing SH. Future studies should explore the effects of distressreducing therapy on clinical SH.